2019
DOI: 10.3390/ijerph16214092
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting the “Heavy-Using Loyalists of Tomorrow”: An Analysis of the Aims, Effects and Mechanisms of Alcohol Advertising, Based on Advertising Industry Evaluations

Abstract: Restricting alcohol advertising and marketing is a cost-effective intervention for reducing alcohol harms. However, the alcohol industry maintains that advertising does not affect consumption, claiming that its purpose is to help consumers choose brands, it is not aimed at young people, it only promotes “responsible consumption”, and any relationships with consumption are not causal. We reviewed 39 case studies (1981–2016) published by the advertising industry, which evaluate the effects of alcohol advertising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 14 publications
3
32
0
Order By: Relevance
“…For example, social norming has frequently been used in alcohol marketing to encourage consumption; one advertising campaign for lager noted that its "new appeal lay in drinkers' perceptions of it as a 'popular, fashionable lager.'" 85 There are several implications of this analysis. First, there is growing interest in misinformation campaigns and the role of the internet and social media in spreading them, and in how to recognize and prevent them.…”
Section: Discussionmentioning
confidence: 96%
“…For example, social norming has frequently been used in alcohol marketing to encourage consumption; one advertising campaign for lager noted that its "new appeal lay in drinkers' perceptions of it as a 'popular, fashionable lager.'" 85 There are several implications of this analysis. First, there is growing interest in misinformation campaigns and the role of the internet and social media in spreading them, and in how to recognize and prevent them.…”
Section: Discussionmentioning
confidence: 96%
“…It should also be noted that the elevated hazard in the 2014 over the 2007 survey was higher among females than males (HR = 2.20 in females and 1.10 in males). It is evidence that the alcohol industry targets marketing efforts toward youth in general, and especially young women (Maani Hessari et al, 2019) by using products with mild alcohol content, colorful appearance and packaging, and fruity flavors to appeal to young women. Our previous study in Thai adolescents also found increasing trends of alcohol consumption among females (Assanangkornchai et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…They can also still access the adult content in any media and are therefore “legally” watching all of the TV programs that other adults watch. Because they will soon become legal consumers, this group is a particular target for marketing [6,7], and it is no coincidence that, for example, alcohol companies sponsor college sports. As such, 18‐ to 20‐year‐olds are probably as, or more, exposed to alcohol marketing as the older adults in the study [8].…”
Section: Declarations Of Interestmentioning
confidence: 99%